2008
DOI: 10.1007/s11832-008-0099-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Taylor spatial frame in adolescent Blount's disease: Is fibular osteotomy necessary?

Abstract: Background The standard treatment of adolescent Blount disease includes proximal tibial osteotomy and osteotomy of the fibula. Some believe that the fibula should also be fixed to prevent migration and subluxation. The purpose of the current study was to examine the results of treatment of patients with adolescent tibia vara treated by tibial osteotomy and Taylor spatial frame (TSF) without fibular osteotomy. Methods Correction of deformities was performed on eight patients (ten tibias) with adolescent Blount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
3
28
0
2
Order By: Relevance
“…In the same article, 100 % of the patients had problems with pin-site infection. The high incidence of this complication has been confirmed by other authors [16,17,19,23]. Leg lengthening was required in one of our cases, but the discrepancy existed before the double corrective osteotomy.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the same article, 100 % of the patients had problems with pin-site infection. The high incidence of this complication has been confirmed by other authors [16,17,19,23]. Leg lengthening was required in one of our cases, but the discrepancy existed before the double corrective osteotomy.…”
Section: Discussionsupporting
confidence: 82%
“…The use of the Ilizarov Frame [15][16][17], the Taylor Spatial Frame [18][19][20], and a Multi-Axial Correction external fixation system [21] are modern therapeutical options, although significantly more expensive than our procedure. These systems enable gradual correction [20], in contrast to our cases, for whom correction was imminent.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,[21][22][23][24][25][26] Manner et al 27 compared IRFs and TSFs in correcting complex limb deformities and found TSF to be superior to IRF. Several studies confirm the accuracy of this method in trauma and developmental deformities.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, this report included patients with both infantile and adolescent Blount disease. Eidelman et al 23 reported eight patients with mild to moderate adolescent Blount disease who underwent successful anatomical correction using the TSF without a fibular osteotomy. Other studies have shown the TSF to be effective in the correction of Blount disease when combined with other procedures such as hemiplateau elevation and epiphysiodesis.…”
Section: Tibia Varamentioning
confidence: 99%
“…Although these two clinical entities prognostically cannot be compared, the treatment was successful in both patient populations. 23 18,19 TSF has been shown to perform comparably to an Ilizarov fixator in treating Blount disease.…”
Section: Tibia Varamentioning
confidence: 99%